LBPS 01-11 EVALUATION OF THYROID STIMULATING HORMONE AND FREE THYROXINE AND THEIR CORRELATIONS WITH OTHER BIOMARKERS IN SUDANESE PRE-ECLAMPTIC CASES. (September 2016) - Beheiry, Hind; Awooda, Hiba; Rayis, Duria; Ali, Ibtisam; Saeed, Amal
Abstract : Objective: This study was to assess changes in serum Thyroid Stimulating Hormone (TSH) and Free Thyroxine (FT4) in pre-eclamptic cases compared to second-half normal pregnant and non-pregnant Sudanese women and its correlations to other biomarkers. Design and Method: This was a case-control study (2008–2010), in Omdurman Maternity Hospital, Sudan. The pre-eclamptic cases (72) were compared to control second-half normal pregnant (96) and non-pregnant (63) Sudanese women. The groups were matched. The clinical and laboratory investigations were undertaken. TSH was measured by two-site sandwich immunoassay and Free T4 by competitive immunoassay using chemiluminescent technology. Liver and renal function tests were performed using atomic absorption spectrophotometer (SiemensAdvia2400 Chemistry System Serial No CA12420098and No a12420083). Results: There was a highly significant difference in mean of TSH in mU/L between Pre-eclamptic (2.52 ± 1.15) and Non pregnant (1.36 ± 0.71) (P-value = 0.000), between Pre-eclamptic (2.52 ± 1.15) and Pregnant (1.53 ± 0.79) (P-value = 0.000), but no significant difference between Non pregnant (1.36 ± 0.71) and Pregnant (1.53 ± 0.79) (P-value = 0.237). There was a highly significant difference in mean of FT4 in pmol/L between Non pregnant (16.11 ± 2.02) and Pregnant (13.55 ± 2.09) (P-value = 0.000), between Non pregnant (16.11 ± 2.02) and Pre-eclampsia (13.96 ± 2.18) (P-value = 0.000), but no significant difference between Pregnant (13.55 ± 2.09) and Pre-eclampsia (13.96 ± 2.18) (P-value = 0. 213). TSH, in pre-eclampsia, has significant correlations correlations with serum uric acid, serum albumin and Serum Aspartate transferase (AST) U/L (Table 1). Conclusions: This study revealed that TSH and FT4 were significantly increased in pre-eclamptic cases when compared to pregnant and non-pregnant women. Figure. No caption available.